1949
DOI: 10.1021/ac60036a004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dibasic Acids in Alkyd Resins

Abstract: the aliphatic anilides, the amides do not show any evidence of a zigzag structure when the longest spacings are plotted against the number of carbon atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1951
1951
1972
1972

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Chlorinated diphenyl affects neither the phthalic nor the vinyl determination. If potassium chloride is present, the phthalic content can be determined by the Swann lead precipitation procedure (34).…”
Section: Styrene Monomermentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorinated diphenyl affects neither the phthalic nor the vinyl determination. If potassium chloride is present, the phthalic content can be determined by the Swann lead precipitation procedure (34).…”
Section: Styrene Monomermentioning
confidence: 99%
“…The quantitative isolation of aluminum from other elements in ferrous metals remains the principal obstacle to its accurate determination. Complexing or sequestering agents which have been investigated include: the sodium salt of ethylenediaminetetraacetic acid (EDTA) in the presence of potassium cyanide (14), thioglycolic acid (34), ascorbic acid following a mercury…”
Section: Aluminummentioning
confidence: 99%
“…of 1 .V titanous chloride). method of Kappelmeier (2, 9), the volumetric potassium phthalate method of Goldberg (8), the lead phthalate method of Swann (15), or the spectrophotometric method of Shreve and Heether ( 14)-However, when present in a lacquer containing an alkyd resin, nitrocellulose interferes. Unfortunately, the alkyd resin cannot be separated quantitatively from the nitrocellulose by any solvent precipitation method.…”
Section: Determination Of Nitrogen In Nitrocellulosementioning
confidence: 99%
“…DURING the past 10 years several papers have been published dealing with the determination of phthalates. Their authors suggested polarographic (14), spectrometric (9), volumetric (2), or gravimetric methods (8,11).…”
mentioning
confidence: 99%